Mindfulness Based Stress Reduction (MBSR) and its Affect Reduce Stress and Fatigue among Carrier Woman - Norizan, Yusof; Mardiana, Mansor; Haslinda, Hashim (Academia Edu Cendekia Indonesia (AECI), 2024)
This study examines mindfulness techniques in reducing fatigue which in turn reduces stress among working women. This study was conducted on 5 study participants who are career women and also have commitments at home. This study was conducted using qualitative case study techniques. The results of the study found that the main cause of the fatigue problem faced is not entirely from the workplace, but rather it starts from the individual and at home when a woman has a hypo emotional tank problem that causes them to feel unappreciated. The effect of this feeling causes a state of negative emotion to be brought to the workplace which ultimately causes increased stress and reduced work productivity. This study also found that, after undergoing a mindfulness session, most of them feel calm and able to think to value themselves which automatically causes the fatigue and stress they face to decrease.